A heavy inheritance: the tengelmann feud - Hollweg, Stephan Johannes (2021)
The case study highlights the criticality and challenge of succession planning in family firms. It outlines the vicious family feud following the sudden disappearance of Karl-Erivan Haub, then-CEO of the 5th-generation German family firm Tengelmann, in 2018.Ignited by an overwhelming inheritance tax burden for Karl-Erivan’s descendants, the conflict quickly revealed the mutual distrust between the family branches. Students can learn about the importance of succession planning by understanding the root causes for the escalating dispute to lie in (i) unmoderated conflicts and unhealthy family dynamics,(ii) insufficient estate planning, and (iii) missing family governance structures.